Tratamento conjugado de águas residuárias e lixiviado de aterro sanitário em lagoas de estabilização rasas - Lima, Diego de Farias (2010)
In recent decades there has been increasing concern about water resources due to population growth, increases in water demand and the degradation of water bodies through the release of domestic and industrial wastewater without adequate treatment. In addition to these problems, municipal solid waste (MSW) produces another source of pollution, namely, leachate emanating from sanitary landfill. This study investigated the treatment of wastewater and landfill leachate in 4 series of shallow waste stabilization ponds located at the Experimental Research Station for Biological Sewage Treatment (EXTRABES), of the State University of Paraiba, Campina Grande, Paraiba, Brazil. The experimental system received sewage from the eastern sewerage interceptor of Campina Grande and leachate collected from the sanitary landfill of the city of Joao Pessoa, PB, and pretreatment by process of "ammonia stripping" in a series of shallow lagoons. The experimental period was divided into three phases, depending on the mixtures of substrate used to feed the pond system. In Phase 1, the substrate was only wastewater, in Phase 2, the substrate was comprised a mixture of wastewater and pretreated leachate in a ratio of 99:1, respectively, and in Phase 3 the ratio of sewage to leachate was 98:2. The removal efficiency of organic material indirectly measured as COD and BOD5 in Phase 1 was 29% and 91% in Phase 2, 54% and 95% and in Phase 3 83% and 90 %, respectively. Regarding species richness of microalgae, there was an increase in the number of species along the stabilization pond system, with 12 algal species in the first pond and 29 species in the final pond. The class Euglenophyceae was predominant in ponds 1 and 2, and Chlorophyceae in ponds 3 and 4. The algal density in pond 4, in relation to pond 1 decreased by 82% in Phase 2 and by 92% in Phase 3. The pH and dissolved oxygen levels in the ponds were highest during the day, between 10 e 16 h, with pH above 9,2 and dissolved oxygen above 14 mg/L in pond 2. The combined treatment of wastewater and landfill leachate in a series of shallow ponds would appear to be a promising alternative technology for the future, providing social, economic and environmental advantages, mainly for geographical regions with favorable availability of areas.